Effect of nutritional risk on cognitive function in patients with chronic obstructive pulmonary disease. Issue 2 (February 2021) - Huang, Yiben; Ma, Jiedong; Jiang, Bingqian; Yang, Naiping; Fu, Fangyi; Chen, Xianjing; Liu, Chunyan; Miao, Xiaqi; Mao, Huanhuan; Zheng, Rongrong; Wang, Jianing; Ding, Keke; et al.
Objective: We aimed to clarify the cognitive function of patients with chronic obstructive pulmonary disease (COPD) and different nutritional status. Methods: Among 95 patients with COPD in this retrospective study, we administered the Nutritional Risk Screening 2002 (NRS 2002) and Mini-Mental State Examination (MMSE). We recorded patients' clinical characteristics, comorbidities, and laboratory measurements. According to NRS 2002 scores, patients were divided into two groups: no nutritional risk with NRS 2002 < 3 ( n  = 54) and nutritional risk, with NRS 2002 ≥ 3 ( n  = 41). Results: We found a negative correlation between NRS 2002 and MMSE scores in participants with COPD ( r  = −0.313). Patients with nutritional risk were more likely to be cognitively impaired than those with no nutritional risk. Multivariate logistic regression analysis indicated that malnutrition was an independent risk factor for cognitive impairment, after adjusting for confounders (odds ratio [OR] = 4.120, 95% confidence interval [CI]: 1.072–15.837). We found a similar association between NRS 2002 and MMSE scores at 90-day follow-up using a Pearson's correlation test ( r  = −0.493) and logistic regression analysis (OR = 7.333, 95% CI: 1.114–48.264). Conclusions: Patients with COPD at nutritional risk are more likely to have cognitive impairment.